Migraine: A Review on Its History, Global Epidemiology, Risk Factors, and Comorbidities - Amiri, Parastoo; Kazeminasab, Somayeh; Nejadghaderi, Seyed Aria; Mohammadinasab, Reza; Pourfathi, Hojjat; Araj-Khodaei, Mostafa; Sullman, Mark J. M.; Kolahi, Ali-Asghar; Safiri, Saeid (Frontiers in Neurology, 2022)
Migraine affects more than one billion individuals each year across the world, and is one of the most common neurologic disorders, with a high prevalence and morbidity, especially among young adults and females. Migraine is associated with a wide range of comorbidities, which range from stress and sleep disturbances to suicide. The complex and largely unclear mechanisms of migraine development have resulted in the proposal of various social and biological risk factors, such as hormonal imbalances, genetic and epigenetic influences, as well as cardiovascular, neurological, and autoimmune diseases. This review presents a comprehensive review of the most up-to-date literature on the epidemiology, and risk factors, as well as highlighting the gaps in our knowledge.